Pengaruh Harga, Promosi, Kualitas Produk Terhadap Keputusan Pembelian Pada Produk Hand & Body Lotion Nivea: Studi Kasus pada Pengguna Produk Hand & Body Lotion Nivea di Surabaya - Lilis Nurhalizah; Siti Ning Farida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to see how much influence price, promotion, product quality has on purchasing decisions for Nivea hand & body in Surabaya. Associative research with a quantitative approach used in this research. The data taken from this research was by distributing questionnaires using gform and the number of samples taken to be used as samples was 100 respondents from all users of Nivea Hand & Body Lotion products in Surabaya who had purchased at least 1 time. Nonprobability sampling is the data collection technique used in this research. Data were processed using SPSS version 23 so that data analysis techniques included validity testing, normality testing, reliability testing, classical assumption testing, multiple linear regression analysis and hypothesis testing. The results of this research are that the price variable (X1) has no effect on purchasing decisions, the promotion variable (X2) has an effect on purchasing decisions, the product quality variable (X3) has an effect on purchasing decisions. Simultaneously the variables price, promotion, product quality influence purchasing decisions.